The degree to which teachers of King Abdullah Schools of Excellence practice technological competencies and their relationship to their job performance from their point of view - Alsuhimat, Fadia Mohammad (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the degree to which teachers of King Abdullah Schools of Excellence practice technological competencies and their relationship to their job performance. A questionnaire was developed to collect data and distribute it to the members of the study sample, which included (162) male and female teachers from the King Abdullah Schools for Excellence, The results of the study showed that the degree of possession of technology competencies by King Abdullah Schools of Excellence teachers came to a medium degree, while the level of their job performance came to a high degree, and there was a statistically significant relationship at the significance level (α≥0.05) between the technological competencies in its two dimensions (general technological competencies and special technological competencies) and job performance for teachers of King Abdullah Schools for Excellence. In light of the results obtained, the study recommended the need to increase attention to technological competencies by increasing school teachers’ awareness of the importance of these competencies and their great impact on helping them develop and improve their performance.